Development, optimization and validation of gas chromatographic fingerprinting of Brazilian commercial gasoline for quality control - Flumignan, Danilo Luiz [UNESP]; Ferreira, Fabricio de Oliveira [UNESP]; Tininis, Aristeu Gomes [UNESP]; Lopes, Márcia Nasser [UNESP]; Oliveira, Jose Eduardo de [UNESP] (Elsevier B.V., 2008)
Three-step development, optimization and validation strategy for GC fingerprints of Brazilian commercial gasoline is described. A suitable chromatographic system was selected first. The following step was to improve acceptable chromatographic resolution with reduced analysis time, which is recommended for routine applications. Optimization was carried out using full three-level factorial designs. Optimal conditions were obtained for flow rate, oven ramps, injection volume and split ratio. Finally, several validation parameters were performed. Therefore, a feasible and reliable fingerprint was established to identify Brazilian commercial gasoline quality. This strategy can also be applied to develop fingerprints for quality control of other fuels. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: gas chromatographic fingerprinting; method development; response surface methodology; Brazilian commercial gasoline; quality control